Electrospun PCL Scaffolds as Drug Carrier for Corneal Wound Dressing Using Layer-by-Layer Coating of Hyaluronic Acid and Heparin - Himmler, Marcus; Schubert, Dirk W.; Daehne, Lars; Egri, Gabriella; Fuchsluger, Thomas A. (International Journal of Molecular Sciences, 2022)
Due to its ability to reduce scarring and inflammation, human amniotic membrane is a widely used graft for wound dressings after corneal surgery. To overcome donor dependency and biological variances in the donor tissue, artificial nanofibrous grafts acting as drug carrier systems are promising substitutes. Electrospun nanofibrous scaffolds seem to be an appropriate approach as they offer the properties of permeable scaffolds with a high specific surface, the latter one depending on the fiber diameter. Electrospun scaffolds with fiber diameter of 35 nm, 113 nm, 167 nm and 549 nm were manufactured and coated by the layer-by-layer (LbL) technology with either hyaluronic acid or heparin for enhanced regeneration of corneal tissue after surgery. Studies on drug loading capacity and release kinetics defined a lower limit for nanofibrous scaffolds for effective drug loading. Additionally, scaffold characteristics and resulting mechanical properties from the application-oriented characterization of suture pullout from suture retention tests were examined. Finally, scaffolds consisting of nanofibers with a mean fiber diameter of 113 nm were identified as the best-performing scaffolds, concerning drug loading efficiency and resistance against suture pullout.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Cornea; Drug delivery; Electrospinning; Heparin; Hyaluronic acid; Layer-by-layer coating; Polycaprolactone; Suture retention test; Wound dressing